The Relationship Between Self-Efficacy and Dietary Compliance in Patients with Diabetes Mellitus at Cancar Public Health Center: English - Hepilita, Yohana; Natul, Fransiska Kurniati; Angelina, Rena Putri Theresia (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2025)
Dietary regulation is one of the main pillars in the management of diabetes mellitus. Effective dietary management requires strong commitment and self-discipline from patients to achieve optimal outcomes. This study aimed to examine the relationship between self-efficacy and dietary compliance among patients with diabetes mellitus at Cancar Public Health Center, Manggarai Regency. A quantitative approach with a cross-sectional design was employed, using a total sampling technique involving 30 respondents. Data were analyzed using Kendall’s Tau-b correlation test. The findings revealed that among respondents with high self-efficacy, 13 were compliant with their diet and 2 were less compliant. Among those with moderate self-efficacy, 1 was compliant, 5 were less compliant, and 4 were non-compliant. Meanwhile, respondents with low self-efficacy showed no compliance or low compliance, with 5 individuals categorized as non-compliant. The statistical analysis using Kendall’s Tau-b test demonstrated a significant relationship between self-efficacy and dietary compliance (ρ-value = 0.000). These results suggest that improving self-efficacy in patients with diabetes mellitus is essential to enhance dietary adherence and prevent more severe health complications.